Music and low-frequency vibrations for the treatment of chronic musculoskeletal pain in elderly: A pilot study. - Thom A H Eshuis; Peter J C Stuijt; Hans Timmerman; Peter Michael L Nielsen; André Paul Wolff; Remko Soer (PLoS ONE)
Background Transcutaneous vagal nerve stimulation has analgesic potential and might be elicited by abdominally administered low-frequency vibrations. The objective was to study the safety and effect of a combination of music and abdominally administered low-frequency vibrations on pain intensity in elderly patients with chronic musculoskeletal pain. Methods This trial was an international multicenter, randomized controlled pilot study. Patients at age ≥ 65 years with musculoskeletal pain for ≥ 3 months and a daily pain score ≥ 4 out of 10 were recruited at three centers. They were randomized to receive either a combination of music and low-frequency (20-100 Hz) vibrations administered to the abdomen, or a combination with the same music but with higher frequency (200-300 Hz) vibrations administered to the abdomen. Low-frequency vibrations were expected to result in pain reduction measured with a numeric pain rating scale (NRS). Patients in both groups received eight treatments of the music combined with the vibrations in three weeks. Primary outcomes were safety (Serious Adverse Events) and pain intensity measured at baseline, after the last treatment and at six weeks follow-up. Multilevel linear model analyses were performed to study group and time effects. Results A total of 45 patients were analyzed according to intention-to-treat principle. After 344 treatments, 1 Adverse Event was found related to the intervention, while 13 Adverse Events were possibly related. A multilevel linear model showed that the interaction effect of group by time did not predict pain intensity (F[1, 45.93] = 0.002, p = 0.97) when comparing pain intensity at baseline, after the last treatment and at follow-up. Conclusions The combination of music and abdominally administered vibrations was found to be safe and well tolerated by the elderly patients. However, over time, neither the low-frequency treatment group nor the high-frequency treatment group provided clinically meaningful pain relief. There is no evidence that the low-frequency treatment elicited vagal nerve stimulation. Trial registration The trial was prospectively registered in the Netherlands Trial Register (NTR: NL7606) on 21-03-2019.